A Retrospective Study Of Correlation Between Depth Of Malignant Tongue Ulcer And Cervical Metastasis (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background In India, the oral tongue cancer is the fourth most common type of cancer among all cancers and second most common in cancers of oral cavity in males. Though there are advances in the diagnosis and treatment of the oral malignancies including the tongue, the failure rates in cancer of the oral tongue are high as the tongue malignancy has higher chances of spreading to neck lymph nodes compared with other oral cancers. Method A retrospective review of the case records of 55 patients who underwent surgery for the treatment of carcinoma of the tongue was carried off in the department of General Surgery and Onco-surgery at the GCS Hospital, Ahmedabad to ensure the pattern of cervical lymph node metastasis and to assess the sensitivity of depth of malignant tongue ulcer in predicting its nodal spread.Results Among 55 patients, diagnosed with carcinoma tongue and operated for hemi glossectomy along with MRND, Lymph node metastasis was present in 22 (40%). Out of these 22 patients, the mean depth of invasion was 11 mm. In patients without lymph node metastasis, the mean depth of invasion was 8.3 mm. Chances of cervical lymph node metastasis increases with increment in the depth of malignant tongue ulcer.Conclusion The infiltration depth of the malignant tongue ulcer can be used as an autonomous predictor for the presence of nodal metastasis.
Keywords: Correlation; Cervical Metastasis